2023
DOI: 10.1021/acsenergylett.3c00133
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-Resistant CO2 Reduction Using Reactive Carbon Solutions

Abstract: Electrolyzers that electrochemically convert aqueous (bi)carbonate solutions (solutions containing captured CO2, or “reactive carbon solutions”) into commodity chemicals couple CO2 capture with CO2 conversion. Industrial exhaust streams contain nitrogen oxides (NO x ) and sulfur oxides (SO x ) that form redox-active anions in reactive carbon solutions that can interfere with downstream CO2 reduction. We therefore designed experiments to test how impurities produced from the dissolution of NO x (NO2 – and NO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In contrast to carbonate electrolysis, bicarbonate electrolysis has shown relatively high CO 2 concentration in the outlet, meaning that not all the produced CO 2 is utilized . For context, under the same operating conditions of −100 mA/cm 2 , bicarbonate electrolysis (pH: 8.8) releases approximately five times more CO 2 than that in carbonate electrolysis (pH: 11.8) . Further evaluations revealed significantly low overall conversion efficiencies in carbonate electrolysis: 0.0015% for Cu and 0.0031% for Cu–Ag(0.5) at −100 mA/cm 2 (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to carbonate electrolysis, bicarbonate electrolysis has shown relatively high CO 2 concentration in the outlet, meaning that not all the produced CO 2 is utilized . For context, under the same operating conditions of −100 mA/cm 2 , bicarbonate electrolysis (pH: 8.8) releases approximately five times more CO 2 than that in carbonate electrolysis (pH: 11.8) . Further evaluations revealed significantly low overall conversion efficiencies in carbonate electrolysis: 0.0015% for Cu and 0.0031% for Cu–Ag(0.5) at −100 mA/cm 2 (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…24 For context, under the same operating conditions of −100 mA/ cm 2 , bicarbonate electrolysis (pH: 8.8) releases approximately five times more CO 2 than that in carbonate electrolysis (pH: 11.8). 41 Further evaluations revealed significantly low overall conversion efficiencies in carbonate electrolysis: 0.0015% for Cu and 0.0031% for Cu−Ag(0.5) at −100 mA/cm 2 (Figure S11). These low efficiencies correlate with the high concentration of reactants (5 M K 2 CO 3 ), the substantial flow rate (65 m/min), and overall low conversion of bicarbonate to CO 2 .…”
Section: Bpm Electrolysismentioning
confidence: 99%
“…In-depth research revealed that the type of anion did not affect the in situ generation of CO significantly. Instead, it primarily influenced the conversion of CO 2 to CO. Pimlott et al 31 took into account the scenario of CO 2 capture from flue gas and examined the effects of nitrogen oxides (NO x ) and sulfur oxides (SO x ) existing in the flue gas on the HCO 3 − electrolyzers. The results indicated that SO x did not have a significant impact on the generation of CO.…”
Section: Mechanism Studiesmentioning
confidence: 99%
“…The aqueous medium of a reactive carbon electrolyzer can be modified to affect the reaction environment in ways that are not possible with a gaseous feedstock. Given the impact that bulk and cathode surface pH, electrolyte composition, electrolyte concentration, and additives have on CO2RR, ,, we contend that there is a broad parameter space available for exploration to improve both the reactive carbon electrolyzer as well as the coupled CO 2 capture unit.…”
Section: Co2 and Reactive Carbon Electrolyzer Configurationsmentioning
confidence: 99%